Kegiatan Penilaian Awal Kelayakan Gereja sebagai Tempat Evakuasi dalam Mendukung Kesiapsiagaan Bencana - Andi Prasetiyo Wibowo; Nadia Nonita Permatasari; Bernadeth Jacinta Amara Setyaputri; Charles Simon Paelongani; Clarissa Felicia Chandra Simon; Shasna Rista Aulia (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2026)
Community-based disaster management is an essential strategy for enhancing the resilience of those residing in earthquake-prone regions. This initiative was undertaken by church communities to aid disaster preparedness by utilizing church facilities as temporary evacuation shelters. The primary aim was to ascertain the possibilities and fundamental prerequisites for enabling church facilities to function effectively as emergency shelters. The activities encompassed focus group discussions, direct observations of building conditions, and the development of a preliminary draft for a feasibility evaluation guideline. Furthermore, geographical capacity mapping and an inventory of accessible basic facilities were completed. This program establishes a foundation for creating a systematic and participatory evaluation framework, with the objective of enhancing the social function of churches in emergency response activities.